Ab-initio complex molecular potential energy surfaces by the back-rotation transformation method - Balanarayan, Pananghat; Sajeev, Yesodharan; Moiseyev, Nimrod (Chemical physics letters, 2012)
The imaginary part of the complex potential energy surface (CPES) provides the autoionization, Auger and ICD (Intermolecular Coulombic Decay) ionization decay rates as functions of the variations in the molecular electronic structure and geometry. We introduce here a novel approach which enables the calculations the molecular complex potential energy surfaces by the standard computational algorithms which were originally developed for calculating real PES of stable molecules. As an illustrative numerical example we have calculated the CPES for the molecular autoionization of hydrogen molecule, H2[1Σg+] where the two electrons are doubly excited.